FPGA-Based Adaptive Beamforming System for Improved Wireless Communication Performance - Vaithianathan, Muthukumaran; Shunyee Frank, Ng; Patil, Mahesh; Reddy, Manjunath; Rajasekaran, Senkadir; Udaya Krishnan, M (2024 Asian Conference on Intelligent Technologies (ACOIT), 2024)
The study describes an innovative adaptive beamforming system that improves wireless communication performance through the utilization of field-programmable gate arrays (FPGAs). Field-Programmable Gate Array (FPGA) technology is utilized by the system to implement adaptive beamforming algorithms. The antenna weights are dynamically adjusted by these algorithms to optimize signal reception and reduce interference in real-time. Signal quality, spectrum efficiency, and overall system performance are significantly improved, as indicated by simulations and FPGA prototypes. The system's adaptive design facilitates dependable functionality in ever-changing environments, as opposed to conventional fixed beamforming methodologies. The proposed system is suitable for implementation in real-time scenarios owing to its minimal latency and effective utilization of resources. This research adds to the growing body of knowledge on wireless communication systems by presenting a versatile and effective approach to enhancing signal quality and reception.